The Potential of Java Plum (Syzygium cumini)as Source of Food Natural Antioxidant - Lydia Ninan Lestario (Indonesian Association of Food Technologists, 2003)
Research on Potential of Java Plum (Syzygium cumini) as Source of Food Natural Antioxidant was devided into 3 steps. The first was to prove that the fruit contain anthocyanin, with anthocyanin-betacycmin testing . The second was to compare antioxidant activity from 3 different stages of maturity of the fruit and with BHT. The third was to separate and identify pigments in the fruit extract. First, the fruit was separated from the seed, freeze dried and kept in freezer during the research. Then, freeze dried fruit was extracted (macerated) with methanol-HC1 1% for overnight at 4 °C, and filtered with whatman no 1. This fruit extract was used for all steps of the research, sometimes concentrated with rotary evaporator at 40 °C when necessary. The first step proved that the fruit extract contained anthocyanin. It was showed by the stable ofpigment in HC1 2 M-100 °C for 5 minutes; alteration to green in addition of drops of 2 MNaOH; low to middle Rf value on HC11 %; and middle Rf value on BAW. Antioxidant activity was tested with ferri-thiocyunate method with linoleic acid emulsion system. The results showed that the antioxidant activity of the fruit was influenced by maturity. Ripe (purple) fruit had highest antioxidant activity compared to unripe (red) and young (green) fruit. The antioxidant activity of purple, red, and green fruit were 64.75%, 62.42%, and 29.86% respectively; whereas BHT was 79.45%. 40 Separation of fruit extract on colomn chromatography with silica gel 60 as stationer phase and EtOAc to methanol: water (1:1) as mobile phase showed 3 different pigments: yellow, purple, and red respectively; whereas separation on paper chromatography with BAW showed 3 different spots: red, blue, and purple. It could be concluded that Syzygium cumini contained anthocyanin. The fruit extract had antioxidant activity that influenced by stages of maturity. Ripe fruit had higher antioxidant activity than unripe and young fruit. At least there were 3 kinds of anthocyanin found in the fruit extract.